2016
DOI: 10.1371/journal.pone.0159437
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SNP and SSR Markers in Finger Millet Using Next Generation Sequencing Technologies

Abstract: Finger millet is an important cereal crop in eastern Africa and southern India with excellent grain storage quality and unique ability to thrive in extreme environmental conditions. Since negligible attention has been paid to improving this crop to date, the current study used Next Generation Sequencing (NGS) technologies to develop both Simple Sequence Repeat (SSR) and Single Nucleotide Polymorphism (SNP) markers. Genomic DNA from cultivated finger millet genotypes KNE755 and KNE796 was sequenced using both R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 76 publications
6
40
5
Order By: Relevance
“…Whereas in other types, AGG & AAG in tri, AAAG in tetra and CGTCA in penta type were most frequent in rest of the species. These results were in accordance with the previous reports in finger millet and other major crops as the mining for repeats in genomic region yielded 39 to 66% of AG/CT repeats [9,13]. The comparative low number of di-nucleotide SSRs was attributed to the reason that these repeats were often present in close vicinity of other repeats, especially penta nucleotides forming compound SSRs.…”
Section: Frequency and Distribution Of Tandem Repeatssupporting
confidence: 92%
See 1 more Smart Citation
“…Whereas in other types, AGG & AAG in tri, AAAG in tetra and CGTCA in penta type were most frequent in rest of the species. These results were in accordance with the previous reports in finger millet and other major crops as the mining for repeats in genomic region yielded 39 to 66% of AG/CT repeats [9,13]. The comparative low number of di-nucleotide SSRs was attributed to the reason that these repeats were often present in close vicinity of other repeats, especially penta nucleotides forming compound SSRs.…”
Section: Frequency and Distribution Of Tandem Repeatssupporting
confidence: 92%
“…Although large and diverse germplasm collections are available in both public and private organizations, no concerted efforts have been made to assess the diversity of this species at the molecular level and integrate these results with morphological characterization in breeding programmes for higher yield and disease resistance [6]. The past decade has witnessed continuous efforts towards developing both conventional and EST-SSR markers in finger millet [7,8,5,9]. Studies on comparative genomics have indicated high genomic colinearity between rice and finger millet [10] and cross-transferability of SSR markers from major cereal crops to E. coracana indicated 57% reproducible cross-species/genus amplicons [11] and 73-95% cross-amplification in finger millet from pearl millet SSRs [12].…”
Section: Introductionmentioning
confidence: 99%
“…Out of 92, 80 SNP markers were polymorphic. However, SNP markers also resulted in a low PIC value of 0.29 revealing narrow genetic base of finger millet as reported with SSRs (Gimode et al, 2016). …”
Section: Molecular Markers For Assessing Genetic Diversity Species Rmentioning
confidence: 71%
“…Kumar et al (2016b) identified 23,000 SNPs through genotyping by sequencing (GBS) of 113 diverse finger millet genotypes. Similarly, 23285 SNPs were generated using next-generation sequencing of two cultivated finger millet genotypes, and 92 SNP markers were validated further for genetic diversity in cultivated and wild species of finger millet (Gimode et al, 2016). Out of 92, 80 SNP markers were polymorphic.…”
Section: Molecular Markers For Assessing Genetic Diversity Species Rmentioning
confidence: 99%
“…The knowledge of genetic diversity estimated by molecular markers is essential to select genetically distinct germplasm for hybridization programs. In the absence of finger millet genome sequence, attempts have been made to develop microsatellite markers and single nucleotide polymorphism (SNPs) (Gimode et al, 2016 Microsatellites (also called as simple sequence repeats: SSRs) are still the cost-effective and robust markers that offer high reproducibility and polymorphism. Currently, there are < 300 informative microsatellites in finger millet and a couple of SNP studies (Sood et al, 2016).…”
Section: Introductionmentioning
confidence: 99%